ESTABLISHMENT OF TRAINING SYSTEM OF ARTILLERY UNIT SPECIALISTS IN UZBEKISTAN - Yusupov R.S. (Scholars Digest Publishing, 2023)
The article it is generalized and analyzed system of formation of preparation of experts for artillery divisions in the higher military educational institutions of Uzbekistan.
Keywords: independence, safety and territorial integrity, quality of preparation of military shots, artillery experts, vocational training, vocational training system, quality of trainees, quality of process of training.